Eco Sufism: Pemikiran Amran Waly dan Ibnu Arabi dalam Menjawab Isu Lingkungan Hidup di Indonesia - Handoyo, Budi (Tadabbur: Jurnal Peradaban Islam, 2025)
Environmental problems can be categorized into three main forms: environmental pollution, improper land use, and excessive exploitation of natural resources. These issues arise from a value system that places human interests as the center of the universe (anthropocentrism). This study employs a normative juridical method with an interdisciplinary approach. The presence of Eco-Sufism, as a spiritual approach that integrates Sufism and ecology, aims to foster spiritual awareness in the interaction between humans and the environment. Within the context of Islamic mysticism, Eco-Sufism is understood as a means of drawing closer to the Creator through His creation. This approach emphasizes the internalization of al-Insān al-Kāmil (the Perfect Man) as a reflection of Divine attributes, which should be embodied by government officials and law enforcement authorities—police, prosecutors, and judges—in upholding justice and legal protection for environmental sustainability. The effectiveness of environmental law enforcement can only be achieved when the values of Sufism and ṭarīqah are implemented within the moral consciousness of law enforcers. Abuya Amran Waly’s thought highlights the importance of noble character in the relationship between humans and nature, while Ibn ‘Arabi’s perspective views nature and humanity as the locus of Divine manifestation.